Brown tumor of the mandible – a possible clinical manifestation of primary hyperparathyroidism - Milankov, Andrijana; Mitrović, Milena; Icin, Tijana; Bajkin, Branislav; Milankov, Vukadin (Vojnosanitetski pregled, 2023)
Introduction. One of the possible manifestations of primary hyperparathyroidism (PHPT) is the appearance of a benign bone tumor. We hereby present a case of a young woman whose first clinical manifestation of PHPT was a brown tumor of the mandible. Case report. A 27-year-old female patient was hospitalized at the Clinic for Endocrinology, Diabetes, and Metabolic Diseases due to problems occurring in the form of nausea, exhaustion, the feeling of suffocation, dysphagia, pain in the right ear and the right half of the cheeks, with suspected PHPT. Initial laboratory findings pointed out the high levels of parathyroid (PT) hormone (PTH) and calcium (Ca2+) ions, low levels of vitamin D, and increased parameters of bone metabolism with signs of osteopenia. Cone beam computed tomography revealed the presence of bilateral radiolucent lesions of the mandible. Scintigraphy verified a retrosternal hot focus consistent with PT adenoma. After parathyroidectomy was performed, there was a normalization of PTH values, bone metabolism parameters, and the Ca2+ values. Four months after parathyroidectomy, a significant regression of the mandibular tumefaction was confirmed, clinically and radiologically. Conclusion. Brown tumors are rare first clinical manifestations of PHPT. Owing to their histological similarities with other giant-cell lesions (GCLs), definitive diagnosis is sometimes difficult and is based on a correlation of pathohistological, radiological, and laboratory findings. Due to the spontaneous regression of bone lesions after treatment of the basic cause of PHPT, brown tumors should be considered in the differential diagnosis of any GCLs in order to avoid unnecessary surgical procedures.
Keywords: bone diseases, endocrine; diagnosis; giant cell tumors; hyperparathyroidism, primary; mandible